2022
DOI: 10.1016/j.slasd.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A multiparametric calcium signal screening platform using iPSC-derived cortical neural spheroids.

Abstract: Discovery of therapeutics for neurological diseases is hampered by the lack of predictive in vitro and in vivo models. Traditionally, in vitro assays rely on engineered cell lines grown two-dimensionally (2D) outside a physiological tissue context, which makes them very amenable for large scale drug screening but reduces their relevance to in vivo neurophysiology. In recent years, three-dimensional (3D) neural cell culture models derived from human induced pluripotent stem cells (iPSCs) have been developed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…However, with multi-parametric analysis, the outcome and conclusions can be complex and potentially confusing. For example, the significant effects of a positive control, 4-AP, were found to be within the data cluster of DMSO controls in 3D-hiPSC-derived neuron cultures in a study reported by others [ 37 ]. Further studies with additional reference drugs encompassing additional pharmacological profiles will need to be evaluated using this HTS Ca 2+ -transient assay within hiPSC-derived neurons to confirm if a single parameter (i.e., the peak number) is sufficient and optimal for the determination of drug-induced changes in neural oscillations and potential risk for seizure.…”
Section: Discussionsupporting
confidence: 60%
“…However, with multi-parametric analysis, the outcome and conclusions can be complex and potentially confusing. For example, the significant effects of a positive control, 4-AP, were found to be within the data cluster of DMSO controls in 3D-hiPSC-derived neuron cultures in a study reported by others [ 37 ]. Further studies with additional reference drugs encompassing additional pharmacological profiles will need to be evaluated using this HTS Ca 2+ -transient assay within hiPSC-derived neurons to confirm if a single parameter (i.e., the peak number) is sufficient and optimal for the determination of drug-induced changes in neural oscillations and potential risk for seizure.…”
Section: Discussionsupporting
confidence: 60%
“…A study investigating the effect of methadone on iPSC-derived cortical organoids found disruption of neural growth and suppression of neural electrochemical activity ( 34 ). iPSC derived neural spheroids have been used to screen for neuromodulatory activity and identify drug targets for opioid use disorder ( 35 , 36 ). Other studies have investigated opioid roles in non-neuronal cell types including endothelial cells ( 37 , 38 ) and cardiomyocytes ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…iPSC-derived neuron model systems are particularly attractive as physiologically relevant neurological models, although there has been a surprising lack of standardized maturation and miniaturization procedures for the in vitro systems especially when using low oxygen culturing conditions. However, iPSC-derived neurons have been used in miniaturized formats (i.e., 384 well assay plates) but they focus on using commercially available pre-plated, pre-formed spheroids [ 37 ] matured 9.5 weeks, bulk neuronal differentiation [ 38 ] or co-culturing with astrocytes for extended culturing [ 39 ]. Moreover, as mentioned previously, NeuN has not been commonly used as a neuronal maturation marker in the assay miniaturization process.…”
Section: Discussionmentioning
confidence: 99%